Application of Media Card Sort With Learningapps.org to Practice German Grammar Mastery of Class X MIPA 2 SMA Negeri 7 Malang - Talitha Syahda Anggraeni; Sawitri Retnantiti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
The purpose of this study was to describe students' activities and responses to students' understanding of grammar related to Verben und Konjugation material with Card Sort media with LearningApps.org. This research was helded offline in class X MIPA 2 SMA Negeri 7 Malang. The method used is descriptive-qualitative and data was obtained through observation sheets by two observers and response questionnaires filled out by 35 students. Based on the research results, students are actively involved in learning and are very responsive. During the learning process, this media is carried out through group discussions. This media is also able to assist students in understanding conjugation rules and the group of regelmäβige Verben und unregelmäβige Verben. Students also almost have no difficulty in using the media. Overall, the use of Card Sort media with the LearningApps.org application received a positive response from students. This media is a new learning media for almost all students. In terms of convenience, this media is easy to access and use. In addition, this aspect of media display is interesting and fun. Media Card Sort with LearningApps.org is also enough to motivate students in learning. It's just that a few students are more motivated if there is an assessment and ranking.